(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes modern approaches to enhancing the seismic resilience of buildings and structures in Uzbekistan. The study encompasses seismic modeling, soil-structure interaction, advanced construction materials, and monitoring technologies to develop structural solutions. Based on simulation results, empirical assessments, and economic analyses, practical recommendations are provided. The article also highlights differences between national regulations and international standards, proposing strategic measures to improve seismic safety in Uzbekistan.